An Air‐Stable Copper Reagent for Nucleophilic Trifluoromethylthiolation of Aryl Halides1. Issue 5 (12th December 2012) - Weng, Zhiqiang; He, Weiming; Chen, Chaohuang; Lee, Richmond; Tan, Davin; Lai, Zhiping; Kong, Dedao; Yuan, Yaofeng; Huang, Kuo‐Wei
<x xml:space="preserve">Abstract</x> A series of copper(I) trifluoromethyl thiolate complexes have been synthesized from the reaction of CuF2 with Me3SiCF3 and S8 (see scheme; Cu red, F green, N blue, S yellow). These air‐stable complexes serve as reagents for the efficient conversion of a wide range of aryl halides into the corresponding aryl trifluoromethyl thioethers in excellent yields.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>